Quality Control Practices for Chemistry and Immunochemistry in a Cohort of 21 Large Academic Medical Centers. Issue 2 (29th May 2018) - Rosenbaum, Matthew W; Flood, James G; Melanson, Stacy E F; Baumann, Nikola A; Marzinke, Mark A; Rai, Alex J; Hayden, Joshua; Wu, Alan H B; Ladror, Megan; Lifshitz, Mark S; Scott, Mitchell G; Peck-Palmer, Octavia M; et al.
Abstract: Objectives: In the United States, minimum standards for quality control (QC) are specified in federal law under the Clinical Laboratory Improvement Amendment and its revisions. Beyond meeting this required standard, laboratories have flexibility to determine their overall QC program. Methods: We surveyed chemistry and immunochemistry QC procedures at 21 clinical laboratories within leading academic medical centers to assess if standardized QC practices exist for chemistry and immunochemistry testing. Results: We observed significant variation and unexpected similarities in practice across laboratories, including QC frequency, cutoffs, number of levels analyzed, and other features. Conclusions: This variation in practice indicates an opportunity exists to establish an evidence-based approach to QC that can be generalized across institutions.